Bold New World: The Essential Road Map to The Twenty -First Century - William Knoke; KNOKE (William) (New York Kodansha International, 1996)
William Knoke, investment banker and visionary futurist, believes it is not the much-touted Information Age that best defines the new era, but rather what he names the Placeless Society. Revolutions in communications and transportation are ushering us into the Age of Everything-Everywhere, where people and goods often move instantaneously from one location to another. He shows us that because "near equals far", all the equations by which national power, corporate wealth, and personal influence have been calculated must be radically redrawn. Bold New World examines our rapidly changing society on the eve of the new millennium and foresees the world in the decades to come. Knoke doesn't just describe trends; he analyzes the dynamic forces that link them, which are creating chains of cause and effect already rippling out into the next century. In brief, imaginary episodes that open each chapter, Knoke illustrates how these trends will affect the everyday lives of people around the world, from CEOs to migrant workers. After sketching these lives, he returns to his ever-practical examination of the future, offering hands-on advice on how we may prepare ourselves for what lies ahead.
Keywords: Social Process; Global Tribes; Global Government